PEMODELAN PETA MATERIALITAS INFORMASI PADA LAPORAN KEBERLANJUTAN PERUSAHAAN (Suatu Tinjauan Mengenai Pelaporan Keberlanjutan Industri Perbankan di Indonesia) - Putu Sukma Kurniawan (Universitas Airlangga, 2017)
Corporate sustainability report has become a new paradigm in the evolution of corporate reporting. This study aims to create a map of information materiality contained in the sustainability report of the banking industry in Indonesia.The method used is analyze content of sustainability reports of the banking industry in Indonesia. Data collection is done by looking for secondary data through page of Indonesia Stock Exchange or company official website. Data analysis was done descriptively by analyzing the contents of sustainability report. The analysis is done by comparing the contents of the sustainability report with the disclosure items contained in the GRI G4 reporting standard (Fourth Generation of Global Reporting Initiative), especially in GRI G4 Sector Disclosures Financial Services.The results of this study produce maps containing material information in the sustainability report of the banking industry. The results of this study may contribute to the management of the company to identify the material information that can be submitted to the company's stakeholders. Keyword : Map of Information Materiality, Sustainability Reporting, Sustainability Report, Banking Industry